2021
DOI: 10.2478/jvetres-2021-0062
|View full text |Cite
|
Sign up to set email alerts
|

Histamine contents in raw long-ripening meat products commercially available in Poland

Abstract: Introduction Many consumers seek long-ripening meat products. The availability of these highly distinctive cured pork varieties is continuously expanding and their safety should be subject to monitoring. One of potentially harmful substances in these products is histamine. The presence of this toxic amine is reported in many countries, even in high concentrations. However, the EU has not regulated the permissible histamine content in meat, in a situation at odds with that of regulated fish an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
0
1
Order By: Relevance
“…The histamine concentration results in this study were lower than those obtained by Michalski et al (2021), who found that the histamine concentration of 97 samples of long-ripening meat products untreated by heat in Poland ranged from below the limit of detection to 346.64 mg/kg, where 3.47 mg/kg was the lowest concentration in a positive sample. Histamine was detected in 48 samples (49.5%).…”
Section: Histamine Concentration In Fresh Minced Porkcontrasting
confidence: 94%
“…The histamine concentration results in this study were lower than those obtained by Michalski et al (2021), who found that the histamine concentration of 97 samples of long-ripening meat products untreated by heat in Poland ranged from below the limit of detection to 346.64 mg/kg, where 3.47 mg/kg was the lowest concentration in a positive sample. Histamine was detected in 48 samples (49.5%).…”
Section: Histamine Concentration In Fresh Minced Porkcontrasting
confidence: 94%